Kajian Eksploratori Hubungan Praktik Komunikasi dan Hasil Proyek Konstruksi di Sumatera Barat - Utama, Wahyudi P.; Sikumbang, Nasril; Warman , Hendri; Zulherman, Zulherman; Fuadi, Al Busyra; Agus , Elfida (Institut Teknologi Bandung, 2024)
Communication management is considered as an important factor related to performance improvement in construction projects. This study aims to identify and determine communication management practices (CMP) in construction projects correlated to project outcomes (PO). Data were obtained from 209 questionnaires distributed to contractors and consultants in the West Sumatra province. The research questionnaire was divided into two components the respondent's profile and four PMK factors, namely Information and Communication Technology (ICT), Communication Skills and Competence (CSC), Communication Management Plan (CMP) and Team Work (TW). Each factor has 4-5 statement items. In terms of project results, it was seen from the project scope, cost, time, quality and safety level. Data were analyzed using Principle Axis Factoring (PAF). The next analysis was the Spearman correlation to evaluate the relationship between each CMP factor and PO. The results showed that there was a strong positive correlation between the three CMP factors (ICT, CSC and TW) and PO. Conversely, no relationship was found between the CMP factor and PO. The may not be fully generalized due to some limitations. However, it helps construction practitioners to recognize the communication aspects that could be improved and strengthened to increase performance of the project.